The Influence of Good Corporate Governance and Green Accounting Disclosure on Company Value with Profitability as a Mediating Variable - Istiva Yuan Amelia (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to analyze the effect of Good Corporate Governance (GCG) and Green Accounting disclosure on firm value, with profitability serving as a mediating variable. The study focuses on companies in the mining, energy, and oil and gas sectors listed on the Indonesia Stock Exchange (IDX) from 2020 to 2022. The data used consists of secondary data obtained from financial and sustainability reports. The analysis method applies a Partial Least Square (PLS) approach to examine the relationships among the variables involved. The study results indicate that GCG and Green Accounting significantly influence firm value both directly and through profitability. Additionally, Green Accounting plays an important role in strengthening investor trust in the company, which ultimately enhances firm value. These findings provide insights for companies on increasing firm value through effective GCG implementation and transparent environmental information disclosure.